Positive and negative mood following imaging-guided core needle breast biopsy and receipt of biopsy results. Issue 10 (26th November 2017) - Perlman, Katherine L.; Shelby, Rebecca A.; Wren, Anava A.; Kelleher, Sarah A.; Dorfman, Caroline S.; O'Connor, Erin; Kim, Connie; Johnson, Karen S.; Soo, Mary Scott
Abstract: Positive and negative mood are independent psychological responses to stressful events. Negative mood negatively impacts well-being and co-occurring positive mood leads to improved adjustment. Women undergoing core needle breast biopsies (CNB) experience distress during CNB and awaiting results; however, influences of mood are not well known. This longitudinal study examines psychosocial and biopsy- and spirituality-related factors associated with mood in patients day of CNB and one week after receiving results. Ninety women undergoing CNB completed questionnaires on psychosocial factors (chronic stress, social support), biopsy experiences (pain, radiologist communication), and spirituality (peace, meaning, faith) day of CNB. Measures of positive and negative mood were completed day of CNB and one week after receiving results (benign n = 50; abnormal n = 25). Multiple linear regression analyses were conducted. Greater positive mood correlated with greater peace ( β = .25, p = .02) day of CNB. Lower negative mood correlated with greater peace ( β = −.29, p = .004) and there was a trend for a relationship with less pain during CNB ( β = .19, p = .07). For patients with benign results, day of CNB positive mood predicted positive mood post-results ( β = .31, p = .03) and only chronic stress predicted negative mood ( β = .33, p = .03). For women with abnormal results, greater meaning day of CNB predicted lower negative mood post-results ( β = −.45, p = .03). Meaning and peace may be important for women undergoing CNB and receiving abnormal results.